Membangun Aplikasi Kasir Toko Sepatu Berbasis Visual Basic - Zain, Muhammad Faizal; Wardhana, Muhammad Rifky (Al-DYAS, 2025)
The cashier application could be an advanced arrangement planned to improve the effectiveness of deals frameworks, especially in shoe stores. This considers points to create a Visual Basic-based cashier application to streamline deals forms in shoe stores. The investigate utilizes a subjective strategy, centering on an in-depth investigation of the prerequisites for a useful cashier framework. The application was tried through a few scenarios, counting including things to the cart, altering stock levels, and printing receipts. The test comes about demonstrate that the application capacities as planned, assembly all required functionalities. No noteworthy bugs were found amid during amid Synonyms the testing stage, and the application illustrated steady execution on Windows 10. The conclusion of this think about highlights that the created cashier application successfully addresses the beginning issues recognized. It encourages deals forms, upgrades store proficiency, and gives comfort for both dealers and clients. In this manner, this application is regarded prepared for utilize as a cashier arrangement for shoe stores.